Recent trends in SCADA Power Distribution Automation Systems - Naidu, Hari Kumar; Thanushkodi, K (Bangladesh Journal of Scientific and Industrial Research, 2010)
The objective of the study in this paper is to evaluate the advances in telecommunication, Information Technology and networking which offer SCADA Power supply Distribution automation as a solution to improve power distribution efficiencies. This paper also discusses the result of the indigenously developed prototype hardware and software model utilising the latest embedded technology innovation for SCADA Power Distribution Automation Systems for reliable performance of power system. Keywords: SCADA; Distribution management system; GIS, Distribution automation; Embedded system. DOI: 10.3329/bjsir.v45i3.1531 Bangladesh J. Sci. Ind. Res. 45(3), 205-218, 2010